Anticipatory action: Lessons for the future - Chaves-Gonzalez, Juan; Milano, Leonardo; Omtzigt, Dirk-Jan; Pfister, Daniel; Poirier, Josee; Pople, Ashley; Wittig, Julia; Zommers, Zinta (Frontiers in Climate, 2022)
Climate shocks are causing increasingly severe damage and amplifying humanitarian needs. So far, humanitarian action has been mostly responsive, arriving after a crisis has materialized. With recent advances in forecasting, humanitarian and development organizations have been able to anticipate and respond ahead of crises. “Anticipatory action” (AA) seeks to ensure aid is provided before the peak impact of a shock occurs, reducing suffering and humanitarian needs. The UN Office for the Coordination of Humanitarian Affairs (OCHA) has been developing AA frameworks since 2019, coordinating collective AA and mobilizing finance. To date, these pilots have reached approximately 2.2 million people in Somalia, Ethiopia and Bangladesh. In six countries (Bangladesh, Burkina Faso, Malawi, Nepal, Niger, and The Philippines), frameworks are in place to reach a further 2.3 million people should the triggers be reached. OCHA is facilitating the design of AA plans in Chad, the Democratic Republic of the Congo (DRC), Madagascar, Mozambique and South Sudan. We share lessons from the pilots, focusing on three components: triggers, programming, and financing. We report that triggers must be sufficiently reliable to warrant action and funds disbursement. Forecasts are not available for all countries or hazards, and existing forecasts may not provide desired resolution or skill (accuracy) levels, especially at longer lead times. The timing of action therefore must balance forecast skill against operational needs. Funding is best when it is flexible and includes finance for framework design, evaluation and continued improvements. Finally we discuss the challenges and opportunities in scaling up AA.